If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(9x + 8) + -1logx = log(x + 8) Reorder the terms: glo(8 + 9x) + -1logx = log(x + 8) (8 * glo + 9x * glo) + -1logx = log(x + 8) (8glo + 9glox) + -1logx = log(x + 8) Combine like terms: 9glox + -1glox = 8glox 8glo + 8glox = log(x + 8) Reorder the terms: 8glo + 8glox = glo(8 + x) 8glo + 8glox = (8 * glo + x * glo) 8glo + 8glox = (8glo + glox) Add '-8glo' to each side of the equation. 8glo + -8glo + 8glox = 8glo + -8glo + glox Combine like terms: 8glo + -8glo = 0 0 + 8glox = 8glo + -8glo + glox 8glox = 8glo + -8glo + glox Combine like terms: 8glo + -8glo = 0 8glox = 0 + glox 8glox = glox Solving 8glox = glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1glox' to each side of the equation. 8glox + -1glox = glox + -1glox Combine like terms: 8glox + -1glox = 7glox 7glox = glox + -1glox Combine like terms: glox + -1glox = 0 7glox = 0 Divide each side by '7'. glox = 0 Simplifying glox = 0 The solution to this equation could not be determined.
| 24=6bsquared | | 4x^2X=3 | | X+(.2*X)=8500 | | X+(.2)x=8500 | | X(x^2+13)-6(x^2+13)=0 | | X+.2x=8500 | | (1/81)=9^5x | | x+3+5=-11 | | 3x-5*62=6 | | 100=65t | | -15=9r+1-7n | | 5x+-3=27 | | n=(-i+4j-k)*(i+-2j+3k) | | b-3=2b+4 | | 2x+3=3x-5-3 | | -4817x=10x+20 | | x^2-3x-3/4=0 | | x^2-3x-3/4 | | y-(y*.12)=70 | | 13+4d/13=193 | | 3ln(2x-7)+6=12 | | 2.8=14*x | | 5(2-3x)=55 | | (2xy+y^2)dy+(y^2+x)dx=0 | | x^2+y^2-4x-6y-10=0 | | 7cosx-24sinx=10 | | 6p-10=2p+10 | | 2(5e-4)=12 | | 9x^2-12x=12 | | .6q+q= | | n=(i-2j+3k)-3(-i+4j-k) | | n=(i-2j+3k) |